Asymptomatic Right Atrial Thrombosis After Acute Lymphoblastic Leukemia Treatment. Issue 4 (May 2021) - Jarvis, Kirsten B.; Andersson, Nadine G.; Giertz, Mia; Järvelä, Liisa; Lindinger, Olle; Långström, Satu; Niinimäki, Riitta; Palmu, Sauli; Trakymiene, Sonata S.; Tuckuviene, Ruta; Vepsäläinen, Kaisa; Ranta, Susanna; et al.
Abstract : Right atrial thrombosis is a rare, but potentially serious complication of acute lymphoblastic leukemia treatment. We conducted a retrospective multicenter study to assess the incidence, treatment, and outcome of asymptomatic right atrial thrombosis detected at routine echocardiography of children after acute lymphoblastic leukemia treatment in the Nordic and Baltic countries. Eleven (2.7%, 95% confidence interval, 1.4-4.9) of 406 patients had asymptomatic right atrial thrombosis, ranging from 10 to 25 mm at detection. Three patients were treated with anticoagulation. None of the thromboses affected cardiac function, and they showed neither sign of progress nor spontaneous or treatment-related regress at follow-up.